Facile Synthesis Polyethylene Glycol Coated Magnetite Nanoparticles for High Colloidal Stability - Tai, M.F.; Lai, Chin Wei; Hamid, Sharifah Bee Abd (Hindawi Publishing Corporation, 2016)
Polyethylene glycol (PEG) is one of the most frequently used synthetic polymers for surface modifications of magnetite nanoparticles (MNPs) to provide a new opportunity for constructing high colloidal stability. Herein, a facile in situ coprecipitation technique is described for the synthesis of PEG coated MNPs using ammonium hydroxide as the precipitating agent. The structure and morphology of the prepared PEG coated MNPs samples were characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray spectroscopy, thermogravimetric analysis (TGA), and the high resolution transmission electron microscopy (HRTEM). In this study, all samples demonstrated hydrodynamic size in the range of 32 to 43 nm with narrow size distribution. In addition, the magnetic properties of resultant samples were investigated using a vibrating sample magnetometer (VSM) to reveal the superparamagnetic behaviour with saturation magnetization. The saturation magnetization of PEG coated MNPs samples was in the range of 63 to 66 emu/g at 300 K. Interestingly, it was found that 1.0 g of PEG coated MNPs exhibited high colloidal stability in a basic solution (pH = 10) and nitrile (NBR) latex up to 21 days as compared to the unmodified MNPs during the sedimentation test.